2022
DOI: 10.47836/ac.15.1.chapter01ac.id
|View full text |Cite
|
Sign up to set email alerts
|

Visitor’s Intentions to Re-Visit Reconstructed Public Place in Jakarta Tourism Heritage Riverfront

Abstract: This research elucidates the influence of the several elements of the heritage public place on the visitors’ intention to revisit and recommend. The study was derived along the reconstructed riverside tourism area of heritage Kali Besar Corridor, Kota Tua, Jakarta, Indonesia. Without sufficient efforts in maintenance, the heritage area will more likely deteriorate. Many stakeholders were trying to solve those problems by preserving the heritage buildings and reactivating public spaces. Responding to the phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…Other research conducted in Indonesia has shown that the visual qualities, atmosphere, and spaciousness of a place are important in enhancing the attractiveness of cultural heritage. These factors were especially important to young people [24].…”
Section: Heritage Tourism Functionsmentioning
confidence: 99%
“…Other research conducted in Indonesia has shown that the visual qualities, atmosphere, and spaciousness of a place are important in enhancing the attractiveness of cultural heritage. These factors were especially important to young people [24].…”
Section: Heritage Tourism Functionsmentioning
confidence: 99%
“…Posisinya sebagai ibukota negara, Jakarta menyimpan sejarah panjang yang patut dihormati. Nilai historis terwujud dalam peninggalan bangunan dan tempat bersejarah yang dapat menjadi daya tarik wisata [4]- [7]. Pengembangan wisata di DKI Jakarta memang membutuhkan keseriusan.…”
Section: Pendahuluanunclassified